Retrospective Analysis of Social and Educational Research of Informative Training of Future Translators - Yevhen Dolynskyi (Pedagogical Discourse, 2013)
The relevance of the article is characterized by the current needs of information society in the preparation of informative competent professionals, particularly in the field of translation. The article considers the scientific, social and educational views on the formation of informative competence of future interpreters in higher education. The problem of using of information technologies in teaching is analyzed. Various approaches and concepts of translation training are observed. The necessity of future translators using information and communication technologies in the system of professional education, formation of their informative competence are analyzed.